1989
DOI: 10.1101/gad.3.2.212
|View full text |Cite
|
Sign up to set email alerts
|

The promoter-proximal rDNA terminator augments initiation by preventing disruption of the stable transcription complex caused by polymerase read-in.

Abstract: We have examined the mechanism by which transcriptional initiation at the mouse rDNA promoter is augmented by the RNA polymerase I terminator element that resides just upstream of it. Using templates in which terminator elements are instead positioned at the opposite side of the plasmid rather than proximal to the promoter, or conditions where transcription is terminated elsewhere in the plasmid by UV-induced lesions, we show that the terminator's stimulatory effect is not position dependent. Mouse terminator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…In Figure 3B we assayed the same set of LS mutants, again under promoter protection conditions, but this time all of the templates were irradiated with UV light before they were added to the transcription extract. Numerous studies have shown UV damage to the template acts as termination sites for RNA polymerase I (Hackett and Sauerbier 1975;Henderson et al 1989;Labhart and Reeder 1989;Lucchini and Reeder 1989). As shown in Figure 3B, UV irradiation completely rescued the negative effect of LS-7 and LS-8 under promoter protection conditions.…”
Section: In Vitro Transcription Conditions That Favor Promoter Protecmentioning
confidence: 64%
See 1 more Smart Citation
“…In Figure 3B we assayed the same set of LS mutants, again under promoter protection conditions, but this time all of the templates were irradiated with UV light before they were added to the transcription extract. Numerous studies have shown UV damage to the template acts as termination sites for RNA polymerase I (Hackett and Sauerbier 1975;Henderson et al 1989;Labhart and Reeder 1989;Lucchini and Reeder 1989). As shown in Figure 3B, UV irradiation completely rescued the negative effect of LS-7 and LS-8 under promoter protection conditions.…”
Section: In Vitro Transcription Conditions That Favor Promoter Protecmentioning
confidence: 64%
“…One mechanism, which we call "promoter protection," is a mechanism in which the terminator protects the initiation complex at the gene promoter from disruption by elongating polymerase reading through from upstream. Evidence that such a protective mechanism is operative for RNA polymerase I promoters has also been published for mouse (Henderson et al 1989) and for Acanthamoeba (Bateman and Paule 1988).…”
mentioning
confidence: 99%
“…Several mammalian rDNAs contain a Sal box (T0) upstream of the transcription start site (Grummt et al 1986;Labhart and Reeder 1986;Pfleiderer et al 1990). Such terminators seem to prevent transcriptional interference by terminating transcripts initiated in the IGS (Bateman and Paule 1988;Henderson et al 1989) and have been shown to stimulate transcription as well (Grummt et al 1986). Yeast rDNA also contains a T0 terminator, which is, however, in the wrong orientation to mediate termination (Fig.…”
Section: Rnapi Terminationmentioning
confidence: 99%
“…Furthermore, there is a required stereospecific alignment of the UPE and the CPE (35). Although the role of the promoterproximal terminator is not completely understood (8,9,14), one of its functions appears to be the prevention of promoter occlusion (14,15,16). Accurate and efficient transcription initiation by RNA polymerase I requires at least two DNA-binding proteins (5,17,18).…”
Section: Introductionmentioning
confidence: 99%